Pengaruh Manajemen Waktu, Kompetensi, Media Pembelajaran Terhadap Kinerja Guru SMP Di Kota Makassar - Lutfi A. Kadir; M. Irfan Maulana Bima (Jurnal Transformasi Bisnis Digital, 2024)
The purpose of this research is to analyze the extent to which time management, competence and learning media affect the performance of junior high school teachers in Makassar. The study used a structural model with the assistance of AMOS 24 and involved 360 junior high school teachers in Makassar as the sample. The research are findings that time management, competence and learning media have a positive and significant effect on improving the performance the performance of junior high school teachers in Makassar.